The Effect of Competitive Strategy and E-Service Quality on Customer Satisfaction Mediated by Customer Loyalty Among Generation Z Consumers of Shopee - Anang Yugotian; Osly Usman; Munawar Asikin (Journal of Strategic Marketing and Innovation, 2026)
This research aims to investigate the influence of e-service quality and competitive strategies on the satisfaction levels of Generation Z customers on Shopee. A purposive sampling technique was utilized to select 200 respondents from Generation Z, aged between 17 to 27, who have made purchases on Shopee in the last six months. A quantitative methodology, along with a survey instrument, was employed to collect the necessary data. The analysis was conducted using SEM-PLS through SmartPLS software. The results demonstrate that competitive strategy has a positive and significant impact on customer loyalty (β = 0.321, p < 0.05). The satisfactory level of customer through competitive strategy and high-quality e-services. These findings indicate that improving the satisfaction of Generation Z consumers is not only determined directly by competitive strategies and electronic service quality but is also influenced by the level of customer loyalty that has been established. Therefore, Shopee needs to continuously strengthen its competitive strategies and improve the quality of its digital services in order to build sustainable customer loyalty and enhance customer satisfaction.